2013
DOI: 10.2527/jas.2012-6194
|View full text |Cite
|
Sign up to set email alerts
|

Dietary plant extracts alleviate diarrhea and alter immune responses of weaned pigs experimentally infected with a pathogenic Escherichia coli1

Abstract: A study was conducted to evaluate the effects of 3 different plant extracts on diarrhea, immune response, intestinal morphology, and growth performance of weaned pigs experimentally infected with a pathogenic F-18 Escherichia coli (E. coli). Sixty-four weaned pigs (6.3±0.2 kg BW, and 21 d old) were housed in individual pens in disease containment chambers for 15 d: 4 d before and 11 d after the first inoculation (d 0). Treatments were in a 2×4 factorial arrangement: with or without an F-18 E. coli challenge (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

31
126
3
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(162 citation statements)
references
References 38 publications
31
126
3
2
Order By: Relevance
“…In the current study, E. coli challenge significantly impaired piglet performance, resulting in reduced ADG and G : F ratio in the week after the challenge and, consequently, a reduced ADG in the following week. These results are in agreement with those of other authors (Liu et al, 2010;Song et al, 2012;Liu et al, 2013). In our study, PE supplementation improved G : F only in non-challenged piglets with an AD feeding regimen; no further beneficial effect on growth performance was found during the enteric E. coli challenge.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In the current study, E. coli challenge significantly impaired piglet performance, resulting in reduced ADG and G : F ratio in the week after the challenge and, consequently, a reduced ADG in the following week. These results are in agreement with those of other authors (Liu et al, 2010;Song et al, 2012;Liu et al, 2013). In our study, PE supplementation improved G : F only in non-challenged piglets with an AD feeding regimen; no further beneficial effect on growth performance was found during the enteric E. coli challenge.…”
Section: Discussionsupporting
confidence: 94%
“…The effect is particularly strong within 1 week of the E. coli challenge. These findings are in agreement with one recent study that showed an anti-diarrhoeal effect in piglets fed PE (Liu et al, 2013). The effect on faecal consistency may be related to an improved gastrointestinal microbial ecosystem in the PE-supplemented piglets.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These bioactive compounds act as plant survival mechanisms and defense mechanisms in response to environmental stressors, pathogen attack, competing plants and herbivory [43]. Phytocompounds have a large variety of principle actives and their effects expected are several as act on the improvement in the palatability of feed, feed intake, feed digestibility, stimulate the pancreatic secretions to increase endogenous enzyme activity, gut development/health, antimicrobial/antiviral, antioxidative and anti-inflammation effects and immune system that could benefit performance and health of farm animals [17,41,[44][45][46][47][48][49][50][51][52][53][54]. Therefore, pthytocompounds could be used to replace some antibiotic growth promoters [55,56].…”
mentioning
confidence: 99%